Education, industrialization and the end of empire in Singapore - Blackburn, Kevin (Routledge studies in educational history and development in Asia, 2017)
Education, Industrialization and the End of Empire in Singapore examines how the state's use of education as an instrument of economic policy had its origins in the colonial economy and intensified during the process of decolonization. By covering this process the history of vocational and technical education and its relationship with the economy is traced from the colonial era through to decolonization and into the early postcolonial period.